PENGARUH PENERAPAN AKUNTANSI KEPERILAKUAN TERHADAP KINERJA KEUANGAN YAYASAN ST. GABRIEL MAUMERE - Nasbun, Yohanes Baptista; Aurelia, Pipiet Niken; De Romario , Fransiscus (Universitas Nusa Nipa Maumere, 2025)
This research aimed to determine the effect of behavioral accounting implementation on the financial performance of the St. Gabriel Maumere Foundation. The data collection techniques used in this research were questionnaires and documentation. This research was quantitative research with an associative approach. The data analysis techniques used in this research were research instrument testing, classical assumption testing, simple regression analysis, hypothesis testing, and coefficient of determination (R2) testing. The results showed that there was a partial effect of the implementation of behavioral accounting on financial performance. This can be seen from the t-value, which was greater than the t-table value, namely 3,767 > 2,032, and the significance value was smaller than the alpha level used, which was 5% or 0.05, namely 0.00 <0.05, so H0 was rejected, which means that the implementation of behavioral accounting (X) had a significant effect on financial performance (Y).